The Effect of ICM Active Learning Strategies on Students' Mathematics Learning Outcomes in JHS 2 Bangkinang - M. Rico Fahrul; Molli Wahyuni; Adityawarman Hidayat; Ahmad Fauzan; Fauziddin Fauziddin (International Journal of Educational Dynamics, 2021)
The research background is that the learning process is less effective in order to achieve optimal student mathematics learning outcomes due to monotonous learning. This research is an experimental research aimed at knowing the results of students' mathematics learning with Index Card Match (ICM) with conventional students' mathematics learning outcomes. The research population was class VII students of JHS 2 Bangkinang consisting of 2 classes. The research sample was taken by purposive sampling, namely class VII students of JHS 2 Bangkinang totaling 58 people. This type of research is experimental research and the research design is a Pre-test-Post-test control group design. The data was collected using Pre-test and Post-test (Pre-test-Post-test) to measure students' mathematics learning outcomes. The analysis technique is descriptive and inferential statistical analysis technique. The results of the acquisition of descriptive statistics are Pre-test and Post-test. The average score of conventional learning students' mathematics learning outcomes is 41.52. The average score of learning outcomes for students learning to apply theICM is 70.17. The results were confirmed by the independent t-test, obtained a Pvalue of 0.000 which was smaller than the significant level of 0.05, so the hypothesis was accepted. It was concluded that the results of learning mathematics with the ICM strategy were higher than conventional learning. The effect of applying the ICM strategy to the mathematics learning outcomes of class VII students of JHS 2 Bangkinang.